PERAN PENGAWAS DALAM IMPLEMENTASI KURIKULUM 2013 PADA SMA NEGERI DI KABUPATEN TANGGAMUS - Syahruddin Syahruddin; Sulton Djasmi; Irawan Suntoro (9 772338317006)
This study focused on the roles of school superintendents in implementing 2013 Curriculum in Senior High Schools in Tanggamus, with the following sub-focus: (1) the role of the superintendent in monitoring teachers, (2) the role of the superintendent as a supervisor, (3) implementation of the superintendents roles in evaluating teachers in implementing 2013 Curriculum in State Senior High Schools in Tanggamus District. This study used a qualitative approach with a case study design. Data were collected using in-depth interviews, documentation and observation. Respondents or informants were selected using purposive sampling, and followed by snowball sampling. Results of this study were: (1) the monitoring was carried out by including selection of appropriate teaching materials in preparing each plan of learning programs created by teachers. (2) The school superintendents supervised the teachers in order to follow up the results of monitoring. (3) The superintendent in carrying out evaluation towards the teachers performance did not fully fit 2013 Curriculum.Penelitian ini difokuskan pada peran pengawas sekolah dalam melaksanakan Kurikulum 2013 SMA di Tanggamus, dengan mengikuti sub-fokus: (1) peran pengawas dalam pemantauan guru, (2) peran pengawas sebagai supervisor, (3) pelaksanaan peran pengawas dalam mengevaluasi guru dalam melaksanakan Kurikulum 2013 di SMA Negeri di Kabupaten Tanggamus. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Data dikumpulkan dengan menggunakan wawancara mendalam, dokumentasi dan observasi. Responden atau informan dipilih secara purposive sampling, dan diikuti oleh snowball sampling. Hasil dari penelitian ini adalah: (1) pemantauan dilakukan dengan memasukkan pemilihan bahan pengajaran yang sesuai dalam mempersiapkan setiap rencana program pembelajaran yang dibuat oleh guru. (2) pengawas sekolah diawasi guru untuk menindaklanjuti hasil pemantauan. (3) pengawas dalam melaksanakan evaluasi terhadap kinerja guru tidak sepenuhnya fit Kurikulum 2013.Kata kunci: bimbingan, evaluasi, pemantauan, pengawas sekolah